Interactive perceptual and attentional limits in visual extinction. - Shalev, L; Chajut, E; Humphreys, G (2005)
We report a case-study of YE, a 54-year-old person who suffered multiple shell injuries that caused a right-parietal lesion and left hemianopia, almost 30 years ago. We conducted 4 experiments using a basic extinction paradigm in which YE had to report single stimuli presented on the left or right or two stimuli presented simultaneously in both visual fields. We show that extinction was selectively affected both by increasing the relative perceptual salience of the contralesional stimulus and by cueing attention to the contralesional side. The effects of perceptual salience and attentional cueing interacted, with cueing being more effective when the stimuli had relatively high perceptual salience. The data are consistent with attentional and perceptual factors interacting to determine the competition between left and right side stimuli that underlies extinction.